Epidemiology, risk factors, social determinants of health, and current management for non-alcoholic fatty liver disease in sub-Saharan Africa - Spearman, C. Wendy; Afihene, Mary; Betiku, Omolade; Bobat, Bilal; Cunha, Lina; Kassianides, Chris; Katsidzira, Leolin; Mekonnen, Hailemichael D.; Ocama, Ponsiano; Ojo, Olusegun; Paruk, Imran; Tzeuton, Christian; et al. (The Lancet Gastroenterology & Hepatology, 2021)
Non-alcoholic fatty liver disease (NAFLD) is the leading cause of chronic liver disease globally and is estimated to affect approximately 25% of the world’s population. Data about the prevalence and incidence of NAFLD in Africa are scarce, but the prevalence is estimated to be 13·5% for the general population. This is likely to be an underestimate considering the increasing burden of non-communicable diseases, particularly the rising prevalence of obesity and type 2 diabetes, driven by the overlapping challenges of food insecurity, nutritional transition, and associated increased consumption of calorie-dense foods. Establishing the true prevalence of NAFLD, raising public awareness around the risk factors behind the increase in NAFLD, and proactively addressing all components of metabolic syndrome will be important to combat this silent epidemic, which will have long-term health-care costs and economic consequences for the region.
Keywords: Epidemiology; Risk factors; Health; Non-alcoholic fatty liver disease; Sub-Saharan Africa